Computarized Reading Programme for Developing IX-Standard Students’ Reading Comprehension - Dr. K. Ramesh Babu (UICELL, 2022)
This research aims at investigating the effect of a computerized programme on developing IX-standard students’ reading comprehension skills. The targeted reading comprehension skills are prediction, skimming, scanning, recognizing synonyms and antonyms, deducing meaning from context and relating the text to personal experience, opinion or evaluation. The researcher purposively has chosen a sample of 60 ninth-standard students from Arakkonam Block, Vellore District. The participants have been divided into two equivalent groups: each group has 30 students. The researcher has used four tools: 1) a questionnaire for teachers to determine the most important reading comprehension skills for IX-standard students, 2) an achievement test (pre & post), and 3) the suggested computer-based programme for the reading texts. The results of the study revealed that the computer-based programme has been effective to develop the reading comprehension skills of IX-standard students. In light of these results, the researcher recommends that language teachers should use computers as a tool for enhancing students’ reading comprehension. Keywords: reading, computerized reading texts, comprehension skills, etc.